Innovation of Contextual Learning Management Model Based on Local Wisdom In English Language Learning - Mahmud Mahmud; Jaya Dwi Putra; Tubagus Pamungkas (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to examine the innovation of contextual learning management models based on local wisdom and their contribution to improving students' English vocabulary mastery at SMP Negeri 3 Numfor Barat. The research method used was the mixed method, which combines qualitative and quantitative data. Qualitative data were obtained through interviews, observations, and documentation, while quantitative data were obtained from the results of students' pre-test and post-test. The results of the qualitative research show that the planning was carried out collaboratively by involving all school components and considering local cultural values. The implementation of learning was conducted by linking English material to the local culture, which increased students' enthusiasm and participation. The eval_uation was conducted comprehensively and provided constructive feedback. Quantitatively, the analysis results show a significant improvement in scores between the pre-test and post-test, with the average score increasing from 25.26 to 61.32. The Paired Sample t-Test yielded a significance value of < 0.001, indicating a significant difference. These findings conclude that the management of the contextual learning model based on local wisdom is not only culturally relevant but also effective in improving students' vocabulary mastery. This model is recommended as an innovative approach in regions with rich local cultural heritage.